Response and Recovery Times of Elastic and Viscoelastic Capsules in Shear Flow (Communications in Computational Physics, 2018)
Amid the recent interest in the role of membrane viscosity in the deformationof a fluid-filled capsule, we consider the role of various capsule properties (shearelasticity, membrane bending stiffness and viscosity) in determining the response andrecovery times of a spherical capsule in shear flow. These times are determined byfitting exponential functions to results for the Taylor deformation parameter $D_{xy}$. Wefocus on the relationship between the membrane and fluid viscosity ratios, as suggestedby Diaz et al [8], and whether adjustments to the fluid viscosity ratio may beused to approximate the effects of membrane viscosity. Based on its ability to reproduceresponse and recovery times, our results suggest that such an approach holdspromise.